Structural Color Modulation by Controllable Fabricating of Two-Dimensional Metal Nanoarrays - Xiu Li; Lingzhi Liu; Yuchen Ren; Jiong Liang; Min Huang (IEEE Photonics Journal)
The structural coloration of two-dimensional photonic crystals has always been a hot topic in recent research. However, how to control the arrangement of nano particles in two-dimensional periodic structure so as to produce specific hue of structural colors with stable physical properties, have become key research content. In order to overcome this drawback, a method of utilizing plasma etching treatment to create structural color modulation on two-dimensional colloidal crystal surfaces by changing the etching power has been proposed. Colors as orange red, yellow, green and blue are obtained with different plasma etching power on planar hexagonal packed structure. The effects of plasma etching power and sizes of PS particles on the optical properties are studied. As a result, the color of samples distributed counterclockwise around white point with increasing the plasma etching power on the a* - b* plane, and changed from orange to blue. Moreover, the diffraction spectrum is also experimentally investigated, and exceed the sRGB gamut boundary. This research can be used in the applications of green printing, anti-counterfeiting and other related fields with low cost.